Evaluating systemic immune-inflammation index in patients with implantable cardioverter defibrillator for heart failure with reduced ejection fraction. (3rd October 2022) - Hayiroglu, M; Cinar, T; Cinier, G; Pay, L; Yumurtas, A C; Tezen, O; Eren, S; Kolak, Z; Cetin, T; Cicek, V; Tekkesin, A I
Abstract: Background: Pro-inflammatory pathways play a serious role in the follow-up of patients with intracardiac defibrillator (ICD) for heart failure reduced with ejection fraction (HFrEF). A newly defined index, which is named as systemic immune-inflammation index (SII), has been recently reported to have prognostic value in patients with cardiovascular disease. Purpose: The aim of this investigation is to evaluate the value of SII in terms of its association with long-term mortality and appropriate ICD therapy during in 10-year follow-up. Methods: This retrospective study included 1011 patients with ICD for HFrEF. The study population was divided into two groups according to optimal cut-off value of SII to predict long-term mortality. The long-term prognostic impact of SII on these patients were evaluated in terms of mortality and appropriate ICD therapy. Results: A receiver operating characteristic curve analyses of systemic immune-inflammation index, platelet-to-lymphocyte ratio and neutrophil-to-lymphocyte ratio in long-term mortality and appropriate intracardiac defibrillator therapy for patients intracardiac defibrillator for heart failure reduced with ejection fraction were presented in Figure 1A and 1B respectively. The patients with higher SII had significantly higher long-term mortality and appropriate ICD therapy. After adjustment for all confounding factors, the long-term mortality had 5.1 higher rates at higher SII. (95% CI: 2.9–8.1). The long-term appropriate ICD therapy also had 2.0 higher rates at higher SII (95% CI: 1.4–3.0). Kaplan Meier survival analysis of patients according to the systemic immune-inflammation index was presented in Figure 2. Conclusion: SII, calculated using neutrophil, platelet, and lymphocyte counts, may be an independent predictive marker for both long-term mortality and appropriate ICD therapy in patients with HFrEF. Funding Acknowledgement: Type of funding sources: None.